Gen Z around the world : understanding the global cohort culture of Generation Z - Seemiller, Corey; Grace, Meghan (Emerald Publishing Limited, 2024)
As Generation Z transitions into adulthood, communication, technology, commerce, education, politics, health, travel, and work have become increasingly globalized. But, most studies about Generation Z have been conducted independently by researchers in various countries regarding their specific populations. While this is useful from a national perspective, these studies typically employ different methodologies, survey questions, and even timing, making it challenging to compare data across geographic and cultural boundaries. More so, it becomes challenging to gain an understanding of the global Generation Z cohort. Gen Z Around the World, however, incorporates research from eighty-one countries to provide a holistic view of Generation Z. The researchers present chapters on everything ranging from communication, happiness, and learning styles to emotional wellbeing, career values, and social change. Learning about Generation Z from a worldwide perspective can expand our understanding to better work with, engage with, supervise, and educate young people in every corner of the globe.